PERAN DAKWAH LEMBAGA EL-PSIKA ALAMIEN PRENDUAN TERHADAPPERUBAHAN KEPRIBADIAN MASYARAKAT - Suhendi Suhendi (Al-Amien Prenduan for Islamic Institute, 2021)
Appropriate with the goals of Islamic Da’wa. In this case, reminding the important of Islami, Tarbawi and Ma’hadi life on a circle of people in Pragaan laok, so that way, El-PsikA has an important role to change the public personality especially for the people who has stern personality through the process of Da’wa given by the foundation. According to the description above, the researcher found a unique which was becoming a problem that interested to research. One of the unique is, although most of them have a stern personality, they could change their personality by the Da’wa from the El-PsikA foundation. For the more to discover about the role of Da’wa El-PsikA foundation, the researcher used qualitative field rapprochement. This rapprochement is using interview, observation and documentary method. This method will be processed by the researcher to get data and information. The subject of this research are from the organizers of El-PsikA Foundation and the Pragaan Laok society. For the validity of data, the researcher used triangulation with two ways; compare the result of observation with the result of interview with the triangulation each method that is comparing the situation and a perspective with the opinions and other perspective.In finding data, the researcher found that the Da’wa of El-PsikA foundation has role for Pragaan laok Society with some rapprochement methods, they are;offering rapprochement, rapprochement with Hikmah,andrapprochement with Mau’idah al-Hasanah. Meanwhile, the rapprochement of Da’wa in El-PsikA foundation Al-Amien Prenduan for fixing the social personality is inviting people approach to Allah swt spiritually with the guidance of DzikrBhatiniahor in other word called as Dizkrin two dimensions that included reciting Shalawatand Istighfarso that both can guard people all day long. By this Dizkrguidance, people will increase their spirituality which has connection with the faith for Allah swt.